Pandangan Politik Jamaludin Al-Afghani Dalam Merefleksi Kehidupan Politik Islam Di Indonesia - Hayumi, Hayumi; Elenita Drihestyawati; Mila Aulia Rahayu (Desanta Publisher, 2024)
This article discusses Jamaluddin al-Afghani's political views in reflecting on Islamic political life in Indonesia. This research uses a type of research library research that examines the pluralist Islamic education paradigm as an alternative to religious integration. Researchers using qualitative research methods are intended to be able to explain phenomena in as much depth as possible by collecting data that shows aspects of the depth and detail of the data studied. This depth is the basis for researchers in studying Indonesian Islam in this philosophical aspect. The results of this research show that Jamaluddin al-Afghani's thoughts related to politics and statehood are very appropriate to be used as reflection, for example, Jamaluddin thinks about unity, inclusiveness, knowledge and wisdom